Pengaruh Harga, Kualitas Produk, Dan Brand Love Terhadap Loyalitas Pelanggan Pada Minimarket Indomaret - Evi Ambarwati; Tin Agustina K; Yunus Handoko (STIE Mandala Jember, 2020)
Modern retail business with the concept of minimarket has experienced a very significant development. Behaviors and lifestyles of consumers who prioritize self service also contribute to the development of the concept of a minimarket, especially in this case are Indomart which is not only a minimarket that provides daily necessities, but also as a cafeteria. The price competition, product quality and brand love of minimarket these days, prioritize customer loyalty.The purpose of this study was to determine and analyze: (1) the effect of prices on customer loyalty in Indomaret GKB-Gresik, (2) the effect of product quality on customer loyalty in Indomaret GKB-Gresik, and (3) the influence of brand love on customer loyalty in Indomaret GKB-Gresik. This research is a field of research conducted using a quantitative approach to Indomart customers who make purchases more than once. The research population is Indomaret GKB - Gresik customers with 100 respondents using accidental sampling method. The data obtained were analyzed using research instrument testing and research hypothesis testing using Statistical Package for the Social Sciences (SPSS) analysis. The results showed that (1) price had a significant effect on customer loyalty at Indomaret GKB - Gresik, (2) product quality had a significant effect on customer loyalty at Indomaret GKB - Gresik, and (3) brand love had a significant effect on customer loyalty at Indomaret GKB – Gresik.